AN INTRODUCTION TO MPEG-4: PENGANTAR MPEG-4 - Yanty Rumengan (Universitas Papua, 2014)
In 2005 MPEG-4 is the latest generation in multimedia codec. MPEG-4 was initially discovered in the year 1998 to overcome the obstacles of MPEG-1 and MPEG-2. However MPEG-4 was not officially recognized until the year 2002. The MPEG-4 standard can be applied to many applications because it contains the ability of scene-based presentation, natural and synthetic object coding, power script, java-language support and network transparent integration [1]. MPEG-4 is the extended version from the final one MPEG-1 and MPEG-2 which means also part of the working group of ISO/IEC developed by Motion Picture Experts Group in charge of the development of international standards for compression, decompression, processing and coded representation of moving picture, audio and both of the combination.